Elevation of sE-Selectin Levels 2–24 Months following Gestational Diabetes Is Associated with Early Cardiometabolic Risk in Nondiabetic Women - Alina Sokup; Barbara Ruszkowska; Barbara Góralczyk; Krzysztof Góralczyk; Marek Szymański; Marek Grabiec; Danuta Rość (International Journal of Endocrinology)
Objective. We hypothesised that the endothelial dysfunction is associated with early glucose dysregulation and/or atherosclerosis risk factors in nondiabetic women with a previous history of gestational diabetes (pGDM). Material/Methods. Anthropometric parameters, glucose regulation (OGTT), insulin resistance (HOMA), lipids, biomarkers of endothelial dysfunction, and inflammation were evaluated in 85 women with pGDM and in 40 controls 2–24 months postpartum. Results. The pGDM group consisted of 67% normoglycemic women (pGDM-N) and 33% with prediabetic state (pGDM-P). The BMI, waist circumference, fasting and 2 h glucose (OGTT), soluble adhesion molecules, tissue plasminogen activator antigen, high sensitivity C-reactive protein, total-, LDL-cholesterol, and triglycerides/HDL-cholesterol ratio were higher in the pGDM women compared with the controls. After adjustment for BMI and fasting glucose, only higher triglycerides, higher TG/HDL and lower HDL-cholesterol were associated with pGDM. The pGDM-P differed from pGDM-N for only higher triglycerides and TG/HDL. The plasma level of sE-selectin was not independently associated with glucose concentration in pGDM group. sE-selectin level correlated with triglycerides, TG/HDL, plasminogen activator inhibitor-1 antigen, and sICAM-1. Conclusions. sE-selectin level correlated with components of metabolic syndrome, but only the atherogenic lipid profile was independently associated with a previous history of GDM in nondiabetic women 2–24 months postpartum.